Effect of combined Moringa oleifera juice and oxytocin massage on lactogenesis II onset - Lasria Simamora; Mastaida Tambun; Riska Susanti Pasaribu; Nur Azizah; Mediana Br Sembiring; Misno Misno (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Delayed onset of lactogenesis II often triggers early formula feeding, which hinders the success of exclusive breastfeeding. Nutritional fulfillment and mechanical stimulation are needed simultaneously to optimize prolactin and oxytocin hormones. Purpose: To analyze the synergy between consuming fresh Moringa oleifera (moringa) juice and oxytocin massage on accelerating the onset of lactogenesis II in postpartum mothers. Method: This study used a cross-sectional descriptive comparative-correlational design involving 70 postpartum mothers. This quantitative study used a quasi-experimental design with a posttest-only control group design, conducted in Bangun Rejo Village, North Sumatra, from February to April 2026. A sample of 36 normal postpartum mothers was selected using purposive sampling and divided equally into two groups (n=18 each). The intervention group was given juice from 20 grams of fresh Moringa leaves twice daily and oxytocin massage for 10–15 minutes daily, while the control group received only standard care. Data normality was tested using the Shapiro-Wilk test, and bivariate analysis was performed using the Independent T-Test. Results: The baseline demographic characteristics (age, parity, education, and Body Mass Index) of both groups were homogeneous (p > 0.05). The mean onset time of lactogenesis II in the combination intervention group was significantly faster (34.50 ± 4.25 hours postpartum) than in the control group (56.60 ± 5.80 hours postpartum), with a difference of 22.10 hours. Independent T-Test results showed a highly significant statistical difference (p < 0.001). Conclusion: The synergy between fresh Moringa oleifera juice consumption and oxytocin massage significantly accelerated the onset of lactogenesis II. This dual-action approach efficiently combines the natural galactagogue properties of Moringa oleifera to stimulate prolactin with the neuroendocrine reflex of massage to facilitate milk ejection.